The Role of Financial Technology in Promoting Digital Finances in Algeria (2016-2024) - Abderraouf Abada; Messaoud Boukhalfi; Mohammed Abderrahmane Bentadjine; Abdelfattah Daoudi (Облік і фінанси)
The financial technologies are changing the approach to service delivery in the banking sector. These technologies reduce costs, increase speed, security, and transparency, and enable safer financial services. They also pave the way for financial inclusion by expanding and generalizing financial services, making them accessible to a larger segment of society, particularly those who do not use the traditional financial and banking system. This study aimed to clarify the extent of financial technology's contribution to achieving digital financial inclusion in Algeria through electronic payment methods during the period from 2016 to the first quarter of 2024. To address and analyze the problem, researchers adopted a descriptive-analytical approach to cover various aspects of the topic and to tackle the issue by dividing this study into three main sections: Concepts of financial technology; Concepts of digital financial inclusion; Strategies for enhancing digital financial inclusion in Algeria through financial technologies in the field of electronic payments. The results of the study showed that there is an effective contribution of financial technology indicators in the field of retail electronic payments in Algeria in enhancing levels of digital financial inclusion, reflected in the improvement of: online payment activities, the number of active bank ATMs, payment activity and the number of operating electronic payment terminals (EPT), mobile phone payment transactions, mobile money transfers, and the number of circulating cards, including the "Gold" card and interbank cards (CIB). Along with this, current challenges for further developing digital financial inclusion include: the slow pace of adopting modern technologies in the field of electronic payments; a lack of trust in new payment methods among some users; the absence of insurance for banks in the event of fraud through electronic payments.